2015
DOI: 10.1016/j.jnci.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of imatinib interruption and duration of prior hydroxyurea on the treatment outcome in patients with chronic myeloid leukemia: Single institution experience

Abstract: Duration of prior hydroxyurea had no impact on response or progression free survival, while patients regular on imatinib had statistically significant difference with respect to major molecular response, complete molecular response and progression free survival compared to those who had periods of drug interruption, thus we need more governmental support to supply the drug without interruption to improve the outcome of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
7
0
2
Order By: Relevance
“…The low response rate in our cohort may be due to the delay between diagnosis and treatment. Incomplete adherence to the treatment is also likely to have an impact on the low response rates we observed, as several studies demonstrate that the poor adherence to the treatment is associated with a lower response in CML [22][23][24].…”
Section: Discussionmentioning
confidence: 95%
“…The low response rate in our cohort may be due to the delay between diagnosis and treatment. Incomplete adherence to the treatment is also likely to have an impact on the low response rates we observed, as several studies demonstrate that the poor adherence to the treatment is associated with a lower response in CML [22][23][24].…”
Section: Discussionmentioning
confidence: 95%
“…These results were conflicting to those of Edesa and his colleague. [40] The appropriate explanation of these conflicting results is much longer duration of disease in patients of this study that ranged from 3-120 months.…”
Section: Discussionmentioning
confidence: 71%
“…Figure 3: Kaplan-Meier analysis of the overall survival (OS) probability. Edesa and Abdel-malek [23] showed no statistically significant difference was observed in PFS according to EUTOS score. Marin et al [19] and Jabbour et al [29] evaluated the clinical significance of the EUTOS score and reported both negative findings.…”
Section: Discussionmentioning
confidence: 80%
“…In Egypt, Heiba and Elshazly [22] showed that 17 (30%), 24 (43%) and 15 (27%) patients were in the Sokal low, intermediate and high risk groups respectively in a study including 56 CML-CP patients. Also in Egypt, Edesa and Abdel-malek [23] showed that the majority of the cases had low risk (75%) according to EUTOS scoring system in a study including 60 CML-CP patients. The discrepancy in the reported figures between several studies, including our study, could be due to several factors.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation